Decision support model in failure - based computerized manitenance management system for small and medium industries - Burhanuddin Mohd. Aboobaider, 1970-; Ab. Rahman Ahmad; Fakulti Sains Komputer dan Sistem Maklumat (2009)
Thesis (Ph.D (Sains Komputer)) - Universiti Teknologi Malaysia, 2009